KEPEMIMPINAN PENDIDIKAN TRANSFORMASIONAL DI ERA REVOLUSI INDUSTRI 4.0 - Herman Herman (Jurnal Dedikasi Pendidikan, 2021)
Abstract: This article aims to describe transformational education leadership in the era of industrial revolution 4.0. Education leadership can be transformed through the utilization of information communication technology in managing education institutions. This study is performed as a library research within a qualitative approach by applying phenomenology to analyze the phenomena in the field of education. Data analysis is carried by studying relevant literature to the research problems investigated. The result of study indicated that transformational education leadership in the era of industrial revolution 4.0 is established and developed by a having a shared vision in managing education institutions (visioning), developing inspirational education programs (inspiring), driving teachers and employees’ work motivation (stimulating), facilitating teachers and employees’ professional development (coaching), and building a solid team work with fellow school communities in managing education institution.Key words: education leadership, transformational, industrial revolution 4.0Abstrak: Artikel ini bertujuan untuk mendeskripsikan kepemimpinan pendidikan transformasional di era revolusi industri 4.0. Kepemimpinan pendidikan dapat ditransformasionalkan melalui pemanfaatan kemajuan teknologi, informasi, dan komunikasi dalam pengelolaan lembaga pendidikan. Penelitian ini menggunakan penelitian library research bersifat kualitatif dengan pendekatan fenomenologi dalam menganalisis fenomena dunia pendidikan. Teknik analisis data dengan cara pengkajian literature yang relevan dengan fokus masalah yang dibahas. Hasil penelitian menunjukkan bahwa kepemimpinan pendidikan transformasional di era revolusi industri 4.0 dibangun, dan dikembangkan dengan cara penyamaan visi pengelolaan lembaga pendidikan (visioning), mengembangkan inspirasi program pendidikan (inspiring), menggerakkan motivasi kerja guru, dan karyawan (stimulating), menfasilitasi pengembangan profesionalisme guru, dan karyawan (coaching),   dan membangun tiem work yang solid dengan sesama warga sekolah dalam pengelolaan satuan pendidikan. Kata Kunci: Kepemimpinan Pendidikan, Transformasional, Era Revolusi Industri 4.0